2022
DOI: 10.1002/anie.202116290
|View full text |Cite
|
Sign up to set email alerts
|

N‐Doped Carbon Electrocatalyst: Marked ORR Activity in Acidic Media without the Contribution from Metal Sites?

Abstract: Fe−N−C electrocatalysts have been demonstrated to be the most promising substitutes for benchmark Pt/C catalysts for the oxygen reduction reaction (ORR). Herein, we report that N‐doped carbon materials with trace amounts of iron (0–0.08 wt. %) show excellent ORR activity and durability comparable and even superior to those of Pt/C in both alkaline and acidic media without significant contribution by the metal sites. Such an N‐doped carbon (denoted as N‐HPCs) features a hollow and hierarchically porous architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
104
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 61 publications
4
104
0
Order By: Relevance
“…Among various candidate catalysts under research and development, pyrolyzed Fe–N–C materials are suggested as the most promising PGM-free ORR catalysts. However, the nature of the active catalytic sites is still under debate, hindering their further optimization and application in PEMFCs . Three types of active sites have been reported to exhibit decent ORR activity: metal–nitrogen moieties embedded in carbon (denoted as Fe–N x ), nitrogen–carbon moieties (C–N), and nitrogen-doped carbon encapsulating inorganic metal species . The major difference within three types of active sites lies in the role of Fe, namely, whether the transition metal only stimulates the formation of C–N active sites or is directly involved in catalyzing the ORR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various candidate catalysts under research and development, pyrolyzed Fe–N–C materials are suggested as the most promising PGM-free ORR catalysts. However, the nature of the active catalytic sites is still under debate, hindering their further optimization and application in PEMFCs . Three types of active sites have been reported to exhibit decent ORR activity: metal–nitrogen moieties embedded in carbon (denoted as Fe–N x ), nitrogen–carbon moieties (C–N), and nitrogen-doped carbon encapsulating inorganic metal species . The major difference within three types of active sites lies in the role of Fe, namely, whether the transition metal only stimulates the formation of C–N active sites or is directly involved in catalyzing the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…The concrete switching behavior was shown to strongly depend on the coordination structures of the pristine Fe–N–C catalysts (e.g., the planar Fe–N 4 and the non-planar Fe–N 4+1 prepared under different pyrolysis temperatures and by different precursors), while other factors still remain unexplored. On the other hand, although many studies have corroborated Fe–N x as the ORR active sites, the contribution of C–N active sites cannot be rigorously ruled out . It is unknown to what extent can these metal-free sites contribute to the overall ORR activity and whether a strong interaction between the Fe–N x and the C–N active sites exists. , Direct probing surface intermediates at the co-existed multiple active sites and decoupling the specific roles of different active sites are essential to answer these questions.…”
Section: Introductionmentioning
confidence: 99%
“… 83 E onset = 0.92 V Tafel slope = 65.7 mV dec −1 N-HPCs E 1/2 = 0.92 V 0.1 M KOH power density 158 mW cm −2 (Zn-air battery) Kong et al. 84 E onset = 1.06 V power density 486 mW cm −2 (H 2 -O 2 fuel cell) Fe/NC-700 E 1/2 = 0.854 V 0.1 M KOH 8 h retain 97.7% Zhang et al. 85 (CoS x /N, S-HCS) 700 E 1/2 = 0.87 V 0.1 M KOH 60,000 s retain 59.6% Xiao et al.…”
Section: Applications Of Mof Nanocrystal-derived Hollow Porous Materialsmentioning
confidence: 99%
“…Such N-HPCs feature a hollow and hierarchically porous architecture, which shows excellent ORR activity and durability. 84 When used as cathode catalysts, the N-HPCs demonstrated distinguished power densities of 486 and 158 mW cm −2 for PEMFCs and Zn-air batteries, respectively. Interestingly, Fe sites do not contribute to ORR activity ( Figures 6 A–6C).…”
Section: Applications Of Mof Nanocrystal-derived Hollow Porous Materialsmentioning
confidence: 99%
See 1 more Smart Citation